2015
DOI: 10.1364/ao.54.002023
|View full text |Cite
|
Sign up to set email alerts
|

Optical beam distortions induced by a shock wave

Abstract: The mean intensity and the displacement from the initially given propagation direction of the optical beam passed through the shock wave have been calculated. It has been shown that the spatial inhomogeneity of the refractive index of air caused by the shock wave arising in supersonic flow flowing a conical body can cause the focusing of the beam and strong anisotropic distortions of the intensity distribution in its cross section. The angular displacement of the optical beam from the initially given propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Summing the complex Gaussian functions, the function of a circular aperture could be obtained as [55]   where a is the radius of a circle aperture, At and Bt are the expansion and Gaussian coefficients, respectively, from the [60,61]. At this time, the coefficient Cm in (16)…”
Section: Comparison On Optimization Of Detection Probability Using Circular Aperture Methods and Focusing Mirror Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summing the complex Gaussian functions, the function of a circular aperture could be obtained as [55]   where a is the radius of a circle aperture, At and Bt are the expansion and Gaussian coefficients, respectively, from the [60,61]. At this time, the coefficient Cm in (16)…”
Section: Comparison On Optimization Of Detection Probability Using Circular Aperture Methods and Focusing Mirror Methodsmentioning
confidence: 99%
“…In the early research, many researchers used ray tracing and geometric optics methods, mainly focusing on physical quantities such as optical path differences (OPD) [11][12][13] and Strehl ratios (SR) [14,15]. Some researchers also regard the shock layer as a strongly turbulent medium and use the refractive index power spectrum of atmospheric turbulence to layer the sheath to study the propagation and distortion characteristics of optical beam and the influence on imaging quality [16,17]. The turbulence intensity can reach 10 -12 .…”
mentioning
confidence: 99%
“…From a mathematical point of view, the essence of the ray tracing problem in aerooptics is to solve the ray differential equation of the gas medium in the flowing state [25]:…”
Section: Equivalent Response Model Of Missile-fuze Systemmentioning
confidence: 99%
“…Luo et al [24] proposed a cumulative pulse detection technique. Banakh [25] simplified the fine structure of a flow field by decomposing the flow field into a time-averaged flow field and a pulsating flow field and concluded that a shock wave will cause the beam to focus through numerical simulation. However, research based on numerical methods can only obtain the numerical solution under a single condition, which is not universal when evaluating the detection accuracy of optical detection systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Ding-Hua et al [11] proposed a ray tracing algorithm with variable step size, which could adjust the step size according to the refractive index of the grid and the size of the grid where the ray is located, it could achieve high tracking accuracy and the angular deviation error of tracing could reach about 1%. In 2015, Banakh et al [12] studied the aero-optical effect caused by the beam passing through the shock layer of the hypersonic vehicle cone. It was found that the flight altitude of the vehicle would weaken the deflection effect of the flow field on the beam.…”
Section: Introductionmentioning
confidence: 99%